(untitled) (World Economics and Finance Bulletin, 2024)
The purpose of the current study is to determine organizational culture and how it affects managers of secondary schools’ administrative inventiveness. The researcher employed a descriptive strategy to accomplish the study purpose, and two research instruments were created to assess administrative innovation and organizational culture. The first tool had 32 items, so what came The second instrument (32) Additionally, the researcher established the validity and reliability of the two instruments, and as the study sample consisted of 135 male and female managers, secondary school managers in the Al-Diwaniyah Governorate represented the research population. After analysis, the findings revealed the following: Managers of secondary schools exhibit a statistically significant positive link between administrative inventiveness and organizational culture. Organizational culture generally has a statistically significant impact on administrative creativity. Based on the study’s findings, the researcher made a number of recommendations, one of which was that secondary school managers should attend training sessions to stay up to date on the most recent advancements in organizational culture. Developing a strategy to get beyond the barriers preventing the implementation of administrative creativity’s components and avoiding mindless copying.